Increasing Creativity of the 4th Grade Students at SDN Gebangan Using PjBL Model with TaRL Approach - Pebriyanti, Diantika; Fitrianawati, Meita; Astuti, Dwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Creativity is an important aspect for students that need to be developed in learning. Creativity can help students in developing the ability to think critically, innovatively and problem solving which is essential in facing challenges in the era of globalization. However, recent research has shown a decrease in the level of student creativity at various levels of education. PjBL or Project Based Learning model is a learning model that emphasizes projects or collaborative assignments that are relevant to students' real lives. Meanwhile, the Teaching at The Right Level (TaRL) approach is an approach in which learning is adjusted to the level of understanding of students. This study aims to explore the use of the Project Based Learning (PjBL) model with the Teaching at The Right Level (TaRL) approach in increasing the creativity of fourth grade students. In this study, students will be involved in real projects that will enable them to use critical thinking, collaboration and innovation skills in solving problems. In addition, the TaRL approach will ensure that students gain a solid foundational understanding before moving on to more complex concepts which will provide them with an important foundation from which to develop their creativity. The research method used was classroom action research involving fourth grade students at SD Negeri Gebangan as the main participants. Data will be collected through class observation and creativity tests. The results of this study are expected to provide concrete evidence about the effectiveness of using the PjBL model with the TaRL approach in increasing the creativity of fourth grade students at SD Negeri Gebangan.Keywords: Creativity, PjBL, TaRL